Retinal Vascular Pathology in a Rat Model of Cerebral Small Vessel Disease - Scheifele, Heinrich Maximilian; Ulbrich, Philipp; Garz, Cornelia; Carare, Roxana Octavia; Heinze, Hans-Jochen; Schreiber, Stefanie; Jandke, Solveig (Frontiers in Neurology, 2020)
Introduction. The initial disease stages of hypertensive arteriopathy (HA) and cerebral amyloid angiopathy (CAA), the two main forms of sporadic human cerebral small vessel diseases (CSVD), are too subtle to be detectable on clinical routine imaging. Small vessel disease (SVD) is a systemic condition, affecting not only the brain, but also other organs. The retina appears an ideal marker for the early detection of incipient CSVD. We therefore investigated the retinal microvasculature of the spontaneously hypertensive stroke-prone rat (SHRSP), an animal model of sporadic CSVD. Materials and methods. The brains and retinas of 26 male SHRSP (18 to 44 weeks) were examined histologically and immunohistochemically for the presence of HA phenomena (erythrocyte thrombi, small perivascular bleeds) and amyloid angiopathy (AA). Results. CAA and AA in the retina showed a significant correlation with age (CAA: rho = 0.55, p = 0.005; AA: rho = 0.89, p < 0.001). The number of erythrocyte thrombi in the brain correlated with the severity of retinal erythrocyte thrombi (rho = 0.46, p = 0.023), while the occurrence of CAA correlated with the appearance of AA in the retina (rho = 0.51, p = 0.012). Retinal SVD markers predicted CSVD markers with good sensitivity. Conclusions. These results indicate that SVD also occurs in the retinal microvasculature of SHRSP and the prediction of cerebral erythrocyte thrombi and CAA might be possible using retinal biomarkers. This underlines the important role of the investigation of the retina in the early diagnosis of CSVD.